Density dependence in a seasonal time series of the bamboo mosquito, Tripteroides bambusa (Diptera: Culicidae) - Hoshi, Tomonori (2017)
The bamboo mosquito, Tripteroides bambusa (Yamada) (Diptera: Culicidae), is a mosquito species ubiquitous across forested landscapes in Japan. During 2014 we sampled adult mosquitoes from May to November using a sweep net in Nagasaki, Japan. We recorded and managed our field data using Open Data Kit, which eased the overall process of data management before performing their statistical analysis. Here, we analyse the resulting biweekly time series of the bamboo mosquito abundance using time-series statistical techniques. Specifically, we test for density dependence in the population dynamics fitting the Ricker model. Parameter estimates for the Ricker model suggest that the bamboo mosquito is under density dependence regulation and that its population dynamics is stable. Our data also suggest the bamboo mosquito increased its abundance when temperature was more variable at our study site. Further work is warranted to better understand the linkage between the observed density dependence in the adults and the larvae of this mosquito species.